(untitled) (Ordia Prima, 2025)
The interest, impact and transmission of the Story of Joseph and Aseneth in the Middle Ages is the starting point of this article. This story is an Old Testament apocryphal narrative with the characteristics of a Greek novel, the original version of which dates back to the 1st century AD. The theme centres on the religious conversion of Aseneth, daughter of the priest Potiphar, to her fascination and infatuation towards Joseph. Her renunciation of the Egyptian religion and her later acceptance of Joseph’s faith follows a visit from an angel who purifies her through an intricate ritual characterised by a honeycomb. The main aim of this paper is to establish the relationship between the different versions of this story from its Greek origins, through Latin translations, to its medieval dissemination in Vincent de Beauvais’ Speculum maius. In addition to the previous studies carried out by Pierre Batiffol, Christoph Burchard, Uta Barbara Fink and Marc Philonenko, the more than twenty Latin manuscripts were consulted and studied in order to establish the manuscript tradition of this story. To this ecdotic analysis, which follows the processes and methodology of Critical Edition, we have finally added the edition of the Latin text, as well as the corresponding annotated translation into Spanish.